Metodyki zarządzania projektami współfinansowanymi ze środków unijnych - Biadacz, Renata (Methodologies of project management co-financed by the European Union funds, 2008)
The aim of this paper is to discuss methodologies most often used in project management including projects co-financed by the European Union funds.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 29-38